Inhibition by Inorganic Dopants of γ‐Alumina Chemical Weathering under Hydrothermal Conditions: Identification of Reactive Sites and their Influence in Fischer–Tropsch Synthesis. Issue 12 (16th May 2017) - Abi Aad, Jane; Courty, Philippe; Decottignies, Dominique; Michau, Mathieu; Diehl, Fabrice; Carrier, Xavier; Marceau, Eric
Abstract: Understanding how alumina degradation to boehmite AlOOH can be prevented under hydrothermal conditions is key to design more stable catalysts supported on alumina for Fischer–Tropsch synthesis. We compare the effect of four inorganic dopants to inhibit γ‐alumina chemical weathering under hydrothermal conditions: three metal ions: Mg 2+, Zr 4+, Ni 2+, introduced by impregnation, and nonmetal Si, introduced by the grafting of tetraethyl orthosilicate. Boehmite is formed by a mechanism of dissolution–precipitation. A significant decrease of alumina weathering to boehmite is evidenced for all dopants. For metal ions, the thermal conversion of doped γ‐Al2 O3 into an alumina‐rich mixed oxide or the coverage of the alumina surface by particles of a poorly soluble oxide such as NiO contribute to the stabilization of the solid. Alumina dissolution and degradation are only inhibited fully through Si grafting. IR spectra in the OH stretching region suggest that the most reactive alumina sites toward dissolution are basic Al−OH sites located on lateral facets that are blocked upon Si introduction. Fischer–Tropsch reactivity shows that Co catalysts prepared on Mg 2+ ‐ and Si‐doped supports are less active or, at best, as active as a reference Co/γ‐Al2 O3 catalyst, which is explained by a lower reducibility of CoO on doped supports. The Co catalyst prepared on Mg 2+ ‐doped γ‐Al2 O3 calcined at 900 °C exhibits the best combination of catalytic activity, ease of preparation, and hydrothermal stability. Abstract : Close protection : The formation of surface mixed phases and Si grafting on the lateral facets of γ‐alumina, respectively inhibits and suppresses the alumina transformation to boehmite through a dissolution–precipitation process under hydrothermal conditions.